Uso de moléculas pró-resulutivas como medida terapêutica para tratar infecção por Influenza A e Fibrose Pulmonar - Flavia Rago Gloria Goncalves (2021)
Influenza A is a virus from the Orthomixoviridae family responsible to cause an acute inflammatory disease with high numbers of mortality and morbidity. Nowadays, the most efficient intervention is vaccination and some anti-inflammatory therapies, which become relevant studies that seek new therapeutic strategies to treat that infection. Lung fibrosis is another lung disease with constant activation of the inflammatory process leading to high levels of collagen deposition which can cause functional loss of this organ. It is a chronic disease that can lead to death. Studies that attempt to find effective therapies to treat this disease are relevant once the best strategy against this clinical condition is organ transplant. Recently, the use of pro-resolving mediators has become promising as a treatment for inflammatory diseases. Pro-resolving mediators are molecules produced in the resolution phase of inflammation with anti-inflammatory and anti-fibrotic proprieties responsible for cell clearance and returning to homeostasis. Lipoxin A4 and angiotensin 1-7 are pro-resolving mediators known to decrease not only cell recruitment but also chemokines, pro-inflammatory and pro-fibrotic cytokines. Here, we studied the use of those pro-resolving mediators as therapeutic strategies to treat lung fibrosis and Influenza A infection. We showed that the preventive treatment with angiotensin 1-7, starting one hour before the induction of fibrosis, decreased cell recruitment on days 3, 7 and 21 after the induction and increased the numbers of apoptotic cells. There was a decrease in collagen deposition on days 14 and 21, and an improvement of lung function on day 21. The treatment increased survival as well. Nevertheless, when we tested the therapeutic effect of this molecule in this model, we noticed that its beneficial effect was time dependent. When the treatment started on day 3, after induction of fibrosis, there was no difference in lethality although the treatment decreased cell recruitment and collagen deposition in the lungs of treated animals. But when the treatment started on day 7 after the induction, the beneficial effect of this molecule was completely lost. Then, we decided to test an analog of another pro-resolving mediator, benzo-lipoxin A4, as a treatment for lung fibrosis, however, there was no difference in the analyzed parameters. Once the same pro-resolving mediator shows different effects in different models of diseases, we decided to test the use of benzo-lipoxin A4 as a treatment for Influenza A infection. Animals infected with Influenza A/WSN/33 H1N1 and treated with benzo-lipoxin A4, starting on day 3 post infection, presented an increase in survival and decrease in cell recruitment, levels of IFN- and lung damage. The treatment also decreased the expression of M1 marker – iNOS- and increased apoptotic cells and eferocitosis. These results show a promising therapeutic effect of lipoxin A4 as a treatment for Influenza A infection, contributing to an anti-inflammatory and pro-resolving scenario. Our work also shows the importance of understanding the role of each pro-resolving mediator and to test them as a therapeutic strategy both in acute inflammatory diseases and in chronic inflammatory diseases since they could present different effects in each one of those diseases.